Kinetics and Mechanisms of Oxycondensation Reaction in Methane Molybden-Marganets Zirconium Catalysis - N.I. , Fayzullaev; Sh. B. , Raxmatov (International Journal of Psychosocial Rehabilitation, 2020)
Based on the ultrafine molybdenum-manganese-zirconium-containing powder, an effective catalyst has been developed for the oxidative dimerization of methane. To obtain molybdenum-manganese-zirconium containing compounds, the sol-gel method was used. The particle sizes and chemical composition of the obtained compounds were determined. The use of the synthesized product as a catalyst allows to reduce the temperature of the reaction, the oxidative dimerization of methane and to increase the selectivity of the process. In the presence of the obtained catalyst, the kinetic laws of the oxidative dimerization of methane were studied, and a mechanism and kinetic model of the reaction were proposed on their basis.